Metabolomics and glucose tolerance in pregnancy and postpartum: The PONCH study - Ulrika Andersson-Hall; Anders Bay Nord; Daniel Malmodin; Agneta Holmäng (PLoS ONE, 2025)
Aims Pregnancy induces significant physiological changes, particularly important in obesity (OB) and gestational diabetes (GDM). We aimed to determine metabolite changes and their relation to clinical variables of obesity and glucose metabolism. Methods Serum NMR metabolomics, clinical data, and body composition were determined in normoglycemic normal-weight (NW) (n = 32) and OB (n = 33) women at six time points spanning pregnancy and postpartum. Additionally, 31 GDM women (15 GDM-NW and 16 GDM-OB) were assessed during trimester 3. Results Profound shifts in the metabolome during pregnancy were exemplified by decreased branched chain amino acids (BCAAs) and tyrosine, and increased phenylalanine, succinate, lactate, and pyruvate. Comparison with clinical variables showed strong correlation between BCAAs’ and bodyfat and insulin resistance mainly in the non-pregnant state. Conversely, pyruvate and lactate exhibited robust correlations with bodyfat, insulin resistance, and adipokines during pregnancy. Comparisons in late pregnancy showed higher levels of BCAAs, phenylalanine, lactate, and pyruvate in both obesity and GDM (GDM-NW and GDM-OB). Conclusions BCAAs are elevated in obesity and GDM although may not be directly related to pregnancy-induced insulin resistance. Conversely, pyruvate and lactate appear connected to gestational changes of glucose metabolism where underlying obesity may contribute.